A case of Kaposi varicelliform eruption progressing to herpes simplex virus hepatitis in an immunocompetent patient. (1st July 2018) - Okamoto, M.; Takahagi, S.; Tanaka, A.; Ogawa, A.; Nobuki, H.; Hide, M.
Abstract: Click here for the corresponding questions to this CME article.